Drivers of inequality in South Africa - Janina Hundenborn; Murray V. Leibbrandt; Ingrid Woolard (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
The first democratic elections in 1994 brought about the promise for equal opportunity and an overall improvement of living standards for the majority of the South African population. However, 20 years after the democratization of South Africa, levels of inequality remain stubbornly high. The focused contribution of this paper is to examine the role of income from different sources driving these high levels of inequality, and which ones cause changes over time. We use data from the 1993 Project for Statistics on Living Standards and Development as well as from the National Income Dynamics Study from 2008 and 2014 to assess the role of different income sources in overall inequality and compare snapshots of the level and texture of inequality across time. We start with the static exercise of explaining the role of income sources in driving income inequality at each of the three points in time. With this static picture as a base, we go on to the dynamic exercise of explaining the role of changing income sources in changes in income inequality over time. The static exercise is an update on work that has been done often before. The dynamic exercise is a fresh contribution. We find that over the past 20 years, labour income has been the major contributor to overall inequality but became less dis-equalizing in later periods. A more nuanced decomposition technique within the dynamic decomposition allows us to separate out the effect of changes in household demographics from changes in income sources. Stripping these demographic effects out of the income sources is important. Now, different income sources decrease inequality between 2008 and 2014 in particular, and over the entire post-apartheid period in general.
Keywords: D31; I32; J30; 330; income distribution; inequality drivers; labour markets; South Africa